2015
DOI: 10.1016/j.kjms.2014.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Association between prostatic resistive index and cardiovascular risk factors in patients with benign prostatic hyperplasia

Abstract: We evaluated the relationship between prostatic resistive index (RI) and cardiovascular system (CVS) risk factors in patients with benign prostatic hyperplasia. The study included 120 patients who were attending our outpatient clinic with lower urinary tract symptoms related to benign prostatic hyperplasia. The clinical, laboratory, anthropometric data, and CVS risk factors (hypertension, diabetes mellitus, metabolic syndrome, history of CVS events, and smoking) of the patients were evaluated regarding the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(34 reference statements)
0
3
0
1
Order By: Relevance
“…94 Confounding factors were identified and adjusted for age, sex, smoking, alcohol consumption, sexual activity, UTIs or infections, constipation, exercise, drug intake, race, and menopause. Confounders were adjusted for using logistical regression analysis, 10,63,66,68 multivariate analysis, 24,25,34,46,51,52,77,82 and sensitivity analysis. 22 Restrictions in design were also performed for age and sex; patients were also stratified according to age, 22 menopause, 57 or smoking status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…94 Confounding factors were identified and adjusted for age, sex, smoking, alcohol consumption, sexual activity, UTIs or infections, constipation, exercise, drug intake, race, and menopause. Confounders were adjusted for using logistical regression analysis, 10,63,66,68 multivariate analysis, 24,25,34,46,51,52,77,82 and sensitivity analysis. 22 Restrictions in design were also performed for age and sex; patients were also stratified according to age, 22 menopause, 57 or smoking status.…”
Section: Discussionmentioning
confidence: 99%
“…Demir et al 10 reported positive correlations between MetS and LUTS (OR = 2.4, 95% CI = 1.24-4.59, p = 0.009); however, significance was lost at multiple logistic regression analysis. Baykam et al 25 found no association between LUTS and BMI (kg/m 2 ); only FBG was significant at multivariate analysis (β = 0.001, t = 3.491, p = 0.001). Gao et al 13 found that MetS was not associated with the severity of LUTS (multivariate: OR = 0.97; 95% CI = 0.67-1.39).…”
Section: Summary Of Qualitative Datamentioning
confidence: 91%
“…This group of age (55-70) mostly, will have cardiovascular risk factors placing further burdens on their prostatic blood flow. Prostate RI values are highly linked to overall metabolic syndrome and smoking in addition to BPH [10]. So, we recommend a study upon younger population in conjunction with cardiologists for assessing cardiovascular risk factors, thus excluding all factors than can influence RI other than pathology of BPH.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…При этом у больных с артери-альной гипертонией и гипергликемией, являющимися И ГЕНИТАЛЬНАЯ ХИРУРГИЯ ТОМ 18 / VOL. 18 2 0 1 7 ANDROLOGY AND GENITAL SURGERY компонентами МС, также отмечается ухудшение крово-снабжения ПЖ, что сочетается с увеличением СНМП [42].…”
unclassified